Ø£Ø³Ù„ÙˆØ¨ Ø§Ù„ØÙƒÙŠÙ… ÙÙŠ Ø§Ù„Ù‚Ø±Ø¢Ù† Ø§Ù„ÙƒØ±ÙŠÙ…: Ø¯Ø±Ø§Ø³Ø© ØªØÙ„ÙŠÙ„ÙŠØ© Ø¨Ù„Ø§ØºÙŠØ© - Ferki Ahmad Marlion; Ahmad Dardiri (Lughawiyah: Journal of Arabic Education and Linguistics, 2019)
ÙŠÙ‚ÙˆÙ… Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ø¨ØªØÙ„ÙŠÙ„ Ø¢ÙŠØ§Øª Ø§Ù„Ù‚Ø±Ø¢Ù† Ø§Ù„ÙƒØ±ÙŠÙ… Ø§Ù„ØªÙŠ ØªØªØ¶Ù…Ù† Ø£Ø³Ù„ÙˆØ¨ Ø§Ù„ØÙƒÙŠÙ… .ÙˆØ§Ù„ØºØ§Ù„Ø¨ ÙÙŠ Ø§Ù„ØÙˆØ§Ø± Ø£Ù† ØªÙƒÙˆÙ† Ø§Ù„Ø¥Ø¬Ø§Ø¨Ø© ÙˆÙÙ‚Ø§ Ù„Ù„Ø³Ø¤Ø§Ù„ØŒ ÙˆÙ„ÙƒÙ† Ø§Ù„Ø¨Ø§ØØ« ÙˆØ¬Ø¯ Ø§Ù„Ø¥Ø¬Ø§Ø¨Ø§Øª ÙÙŠ Ø§Ù„Ù‚Ø±Ø¢Ù† Ø§Ù„ÙƒØ±ÙŠÙ… Ù…Ù…Ø§ Ù„Ù… ÙŠØªØ±Ù‚Ø¨Ù‡ Ø§Ù„Ø³Ø§Ø¦Ù„. Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ù…Ù† Ø§Ù„Ø¨ØÙˆØ« Ø§Ù„ÙˆØµÙÙŠØ©. ÙˆÙ„Ø£Ø¬Ù„ Ø°Ù„Ùƒ Ø¬Ù…Ø¹ Ø§Ù„Ø¨Ø§ØØ« Ø§Ù„Ø¨ÙŠØ§Ù†Ø§Øª Ù…Ù† Ø§Ù„Ù‚Ø±Ø¢Ù† Ø§Ù„ÙƒØ±ÙŠÙ… ÙˆØ§Ù„Ù…ØµØ§Ø¯Ø± Ø§Ù„Ø£Ø³Ø§Ø³ÙŠØ© (ØªÙØ³ÙŠØ± Ø§Ù„ØªØØ±ÙŠØ± ÙˆØ§Ù„ØªÙ†ÙˆÙŠØ±ØŒ Ø£Ø³Ù„ÙˆØ¨ Ø§Ù„ØÙƒÙŠÙ… Ù†Ù…ÙˆØ°Ø¬) ÙˆØ§Ù„Ù…ØµØ§Ø¯Ø± Ø§Ù„Ø«Ø§Ù†ÙˆÙŠØ© (Ø£Ø³Ø¨Ø§Ø¨ Ø§Ù„Ù†Ø²ÙˆÙ„). ÙˆÙŠÙ†ØªÙ‡ÙŠ Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ø¥Ù„Ù‰ Ø£Ù† ÙÙŠ Ø§Ù„Ù‚Ø±Ø¢Ù† Ø§Ù„ÙƒØ±ÙŠÙ… 31 Ø£ÙŠØ© ØªØ³ØªØ®Ø¯Ù… Ø£Ø³Ù„ÙˆØ¨ Ø§Ù„ØÙƒÙŠÙ…. ÙˆØ§Ø³ØªØ¹Ù…Ø§Ù„ Ø£Ø³Ù„ÙˆØ¨ Ø§Ù„ØÙƒÙŠÙ… ÙÙŠ Ø§Ù„Ù‚Ø±Ø¢Ù† Ø§Ù„ÙƒØ±ÙŠÙ… ÙŠÙƒÙˆÙ† Ù„Ø£Ø¬Ù„ Ù…Ø±Ø§Ø¹Ø§Ø© Ø£ØÙˆØ§Ù„ Ø§Ù„Ø³Ø§Ø¦Ù„ÙŠÙ† Ø§Ù„Ø¥Ø¬ØªÙ…Ø§Ø¹ÙŠØ© ÙˆØ§Ù„Ù†ÙØ³ÙŠØ© ÙˆØ§Ù„Ø«Ù‚Ø§ÙÙŠØ© ÙˆØ§Ù„Ø§Ù‡ØªÙ…Ø§Ù… Ø¨Ø§Ù„ÙØ±ÙˆÙ‚ Ø§Ù„ÙØ±Ø¯ÙŠØ©ØŒ ÙˆØªÙƒÙˆÙ† Ø§Ù„Ø¥Ø¬Ø§Ø¨Ø© Ø¹Ù† Ø§Ù„Ø£Ø³Ø¦Ù„Ø© Ø¨ØªÙ‚Ø¯ÙŠÙ… Ù…Ø§ Ù‡Ùˆ Ø£Ù‡Ù… Ø¹Ù„Ù‰ Ù…Ø§ Ù‡Ùˆ Ù…Ù‡Ù…ØŒ ÙˆÙ…Ø«Ø§Ù„ Ø°Ù„Ùƒ Ø§Ù„Ø¥Ø¬Ø§Ø¨Ø© Ø¹Ù† Ø§Ù„Ø¢ÙŠØ© "ÙŠØ³Ø£Ù„ÙˆÙ†Ùƒ Ø¹Ù† Ø§Ù„Ø£Ù‡Ù„Ø©" Ø¨Ø¥Ø®ÙØ§Ø¡ Ø§Ù„Ù„Ù‡ ØªØ¹Ø§Ù„Ù‰ Ø§Ù„Ø¨ÙŠØ§Ù† Ø¹Ù† Ø£Ø³Ø¨Ø§Ø¨ ØªØºÙŠØ± ØØ§Ù„Ø§Øª Ø§Ù„Ø£Ù‡Ù„Ø© ÙˆØªÙ‚Ø¯ÙŠÙ… Ø§Ù„Ø¨ÙŠØ§Ù† Ø¹Ù† Ù…Ù†Ø§ÙØ¹Ù‡Ø§ØŒ Ù„Ø£Ù† Ù‡Ø° Ø§Ù„Ø£Ø®ÙŠØ± Ù‡Ùˆ Ø§Ù„Ø£Ù‡Ù…. ÙˆÙ„Ùˆ ÙƒØ§Ù†Øª Ø§Ù„Ø¥Ø¬Ø§Ø¨Ø© Ø¨Ù…Ø§ Ù‡Ùˆ Ø§Ù„Ù…Ø·Ù„ÙˆØ¨ ÙÙŠ Ø§Ù„Ø³Ø¤Ø§Ù„ Ù„ØµØ¹Ø¨Ø© Ø¹Ù„Ù‰ Ø§Ù„Ø³Ø§Ø¦Ù„ ÙÙ‡Ù…Ù‡Ø§ØŒ ÙØ§Ù„Ø¹Ù‚Ù„ÙŠØ§Øª Ø¢Ù†Ø°Ø§Ùƒ ÙƒØ§Ù†Øª Ø¨Ø³ÙŠØ·Ø©ØŒ ÙˆØ§Ù„Ø¹Ù„ÙˆÙ… Ù„Ù… ØªÙƒÙ† Ù…ØªØ·ÙˆØ±Ø©ØŒ ÙÙ„Ù… ØªØªÙˆÙØ±Ù„Ù‡ Ø§Ù„Ù‚Ø¯Ø±Ø© Ø¹Ù„Ù‰ ÙÙ‡Ù… Ø§Ù„Ø¥Ø¬Ø§Ø¨Ø©. ÙˆØ£Ø®ÙÙ‰ Ø§Ù„Ù„Ù‡ ØªØ¹Ø§Ù„Ù‰ ÙƒØ°Ù„Ùƒ Ø¹Ù† Ø§Ù„Ø£Ù…ÙˆØ± Ø§Ù„ØºÙŠØ¨ÙŠØ© Ù…Ø±Ø§Ø¹Ø§Ø© Ù„Ù…Ø³ØªÙˆÙ‰ Ø§Ù„Ù…Ø®Ø§Ø·Ø¨ÙŠÙ† Ø§Ù„ÙÙƒØ±ÙŠØŒ ÙˆÙ„Ø§ ÙØ§Ø¦Ø¯Ø© ÙÙŠ Ù…Ø¹Ø±ÙØªÙ‡Ø§.This research is done to reveal the verses of Alquran al Karim which are connected to Uslub al Hakim in Alquran. This is a qualitative research. The data were collected from Alquran and took tafsir at-tahriir wa attanwiir, usluub alhakiin namuuzaj as the main source and asbabun nuzul as the supporting source. The researcher found there are 31 verses which are connected to Uslub al Hakim, the application of Uslub al Hakim in Alquran al Karim to respect and understand who the questioners are, whether it is about social problem, personal or local habits. Uslub al Hakim also concerns on individual difference, and answers the most important and useful questions. For example, the process of moon creation was hidden by Allah SWT because human being in the era did not have enough capacity to understand it yet. If Allah SWT explains it as they wish, it would be very difficult for them to understand because humanâ€™s thinking skill was very simple and there was no proper knowledge to support it yet at that time. Allah SWT also did not explain in detail about the transcendental things, to appreciate thinking capacity and to avoid useless discussion.